Efeitos audiovisuais na animação: a produção do medo - Pereira, Bibiana Lauretti (2024)
The objective of this work is to analyze the production of fear in current animated films. The research corpus selects three films from 2022 and 2021, namely: Turning Red and Encanto from Disney Studios, and Arcane from Netflix Studios. These three works share significant similarities, such as family relationships involving the main female characters and the conflicts that arise from them. The soundtrack is chosen as the primary focus of influence on the production of fear, along with the issue of childhood trauma experienced and relived by the protagonists. Thus, the theoretical and methodological references bring together, on one hand, studies focused on film sound and/or musicality, such as those of Maria Teresa Alencar de Brito and Maria de Lourdes Sekeff, directed towards children's media, or Rosinha Spiewak’s work on Hitchcockian suspense. On the other hand, psychoanalysis is also called upon, including contributions from British psychoanalysis regarding the child's relationship with the mother and psychoanalytic semiotics for an in-depth analysis of the symptoms in question. The relevance of this proposal is tied to the opportunity to observe fear and childhood trauma in light of new animations